Effect of stenting and mucosal flap preservation on outcome of endoscopic dacryocystorhinostomy - Tai, Evelyn Li Min; Tevaraj, Jessica Mani Penny; Wan Hitam, Wan Hazabbah; Ramza, Ramiza; Abdullah, Baharudin; Hussein, Adil (Press of International Journal of Ophthalmology (IJO PRESS), 2014)
AIM: To determine the effect of stenting and flap preservation on the outcome of endoscopic dacryocystorhinostomy. METHODS: Retrospective study of all endoscopic dacryocystorhinostomy cases performed between 2007 - 2011 at Hospital Universiti Sains Malaysia. A total of 25 cases with nasolacrimal duct obstruction underwent this procedure. Outcome of endoscopic dacryocystorhinostomy was evaluated based on relief of epiphora and anatomical patency by lacrimal syringing and nasal endoscopy upon follow-up at 1, 6 and 12 months post- op. The outcome was considered to be successful only if all three criteria were fulfilled at one year follow - up post - op. Multiple logistic regression was used to determine the association of stenting and flap creation with a successful outcome. RESULTS: Stents were inserted in 13 cases out of 25, and likewise for flaps. The success rate of endoscopic dacryocystorhinostomy at one year post - op was 64% . There was no significant association of stenting with outcome (P = 0. 694), whereas mucosal flap creation was significantly associated with a better outcome (adjusted OR= 7.926; 95%CI: 1. 172-53. 620, P = 0. 034). The main postoperative complication was adhesions, which occurred in 50% of cases. There was no significant association between stenting or flap preservation with complications. CONCLUSION: Preservation of a mucosal flap is significantly associated with a successful outcome of endoscopic dacryocystorhinostomy in nasolacrimal duct obstruction, while stenting is not. Neither stenting nor mucosal flap creation is significantly associated with complications.